The establishment of simple lawsuit rules in business disputes in Indonesia: an challenge to achieve fair legal certainty - Gunawan, Matthew Marcellinno; Fathoni, M Yazid (Journal of Law, Environmental and Justice, 2023)
This study aims to prescribe the importance of rethinking the regulation of the execution of simple lawsuits in the justice system in Indonesia, considering that simple lawsuits have many advantages as an alternative for resolving civil and business disputes. This research is normative legal research with a law approach, a conceptual approach, and a comparative law approach. The countries used for comparison are Singapore, the Netherlands, and the United States. The study results show that legal uncertainty regarding the mechanism of the simple lawsuit court decision is a factor that must be considered if you want a simple lawsuit to be one of the models of dispute resolution in the business and civil disputes that exist in Indonesia. This should be the homework of the government or the Supreme Court in establishing clear rules regarding the procedure for the execution of a simple lawsuit. This is important to do to provide clarity and legal certainty for the parties.